PENGARUH TIME BUDGET PRESSURE, AUDIT TENURE DAN UKURAN KAP TERHADAP KUALITAS AUDIT - Mohamad Alfi Amrulloh; Made Dudy Satyawan (Progress: Jurnal Pendidikan, Akuntansi dan Keuangan, 2021)
In carrying out their duties, auditors must be competence and have to maintain their audit quality to provide trust to stakeholder. However, currently there are many cases that will causes the audit quality to decline. The cases is about financial cases that are still being discussed in public and have connection about audit quality on financial statement. The objective of this study was to determine effect of Time Budget Pressure, Audit Tenure and Audit Firm Size on Audit Quality. This study uses the primary data from questionnaire that was distributed to auditor KAP in Surabaya. Method determination sample used purposive sampling criteria and have 55 sample data can used. Data analysis model is multiple linear regression analysis. The result of this study indicate time budget pressure have positive effect on audit quality, but audit tenure and audit firm size has no effect on audit quality.